Initiatives to boost resilience towards El Niño in Zimbabwe’s rural communities - Matunhu, Jephias; Mago, Stephen; Matunhu, Viola (AOSIS, 2022)
Most Zimbabweans living in rural areas experience acute shortages of water for domestic and agricultural purposes. Household poverty amongst rural inhabitants is also increasing because of factors such as El Niño-induced droughts, overdependence on donor assistance and government’s failure to invest in sufficient water infrastructure. The purpose of this article is to interrogate the initiatives that have been taken to alleviate food insecurity in Zimbabwe’s rural communities. Under the spotlight are the strategies that rural communities and other stakeholders embraced to adapt to the effects of El Niño and to reduce food poverty. We used extensive literature review methodology and explorative qualitative design to investigate how rural communities and other stakeholders in Zimbabwe deal with the issues of food security in the context of persistent El Niño-induced droughts. The results show that rural communities in Zimbabwe continue to experience food security challenges that require collaboration between communities, government, non-governmental organisations (NGOs) and other stakeholders to build resilience against El Niño-induced droughts. Modernising water supply systems and agricultural management systems can improve the efficiency and effectiveness in food production and distribution.